2011
DOI: 10.1166/jnn.2011.3750
|View full text |Cite
|
Sign up to set email alerts
|

Sidewall Functionalization of Carbon Nanotubes Through Electrophilic Substitution

Abstract: We report a general strategy for functionalizing the sidewalls of carbon nanotubes (CNTs), which is based on electrophilic substitution reactions on phenylated CNTs. By using this strategy, four new functionalized CNTs were prepared, including diphenyl ketone, benzenesulfonyl chloride, benzyl chloride and thiophenol modified CNTs. The benzenesulfonyl chloride and benzyl chloride functinalized CNTs could serve as novel initiators for surface-initiated atom transfer radical polymerization. The thiophenol modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Surfactants or additional treatments were often needed to maintain the dispersibility of the products,23 especially when organic solvents were used. In our previous work,24 we have demonstrated that BPO could be used in the surface modification of carbon nanotubes (CNTs) to produce phenyl‐modified CNTs 17c. 25 It is reasonable to believe that a similar reaction can take place on graphene, and the CMG produced by BPO‐promoted conversion (denoted as G BPO ) is also modified by phenyl groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surfactants or additional treatments were often needed to maintain the dispersibility of the products,23 especially when organic solvents were used. In our previous work,24 we have demonstrated that BPO could be used in the surface modification of carbon nanotubes (CNTs) to produce phenyl‐modified CNTs 17c. 25 It is reasonable to believe that a similar reaction can take place on graphene, and the CMG produced by BPO‐promoted conversion (denoted as G BPO ) is also modified by phenyl groups.…”
Section: Resultsmentioning
confidence: 99%
“…The produced G BPO could be well dispersed in various organic solvents, which is desirable for many applications. Furthermore, the attached phenyl moieties may be subjected to various well‐established electrophilic substitution reactions to introduce further modification onto the graphene surface; these reactions have been previously demonstrated on CNT surfaces 24…”
Section: Resultsmentioning
confidence: 99%
“…Zeng et al reported the electrophilic substitution reactions on phenylated CNTs. A new functionalization of CNT sidewalls was realized by including diphenyl ketone, benzenesulfonyl chloride, benzyl chloride, and thiophenol as shown in Figure 24 [196]. Then, Tagmatarchis et al have successfully functionalized SWCNTs through electrophilic addition of chromoform SWCNTs followed by hydrolysis which is allowing the addition of hydroxyl groups to the surface of the nanotubes [197].…”
Section: Brominationmentioning
confidence: 99%
“…Marcelino et al reported that unmodified CNTs presented a conductivity of 510 S/m which decreased as the functionalization degree increased [212]. In contrast, Lau et al [213] Figure 24: Schematic procedure for the electrophilic substitution reaction on p-CNTs and the applications in making hybrid materials [196]. 21 Journal of Nanomaterials changed from sp 2 to sp 3 reinforced state.…”
Section: Properties Of Functionalized Cntsmentioning
confidence: 99%
“…将共价功能化的碳纳米管应用到复 合材料、催化剂载体、电子器件、光学材料及生物医学 等领域当中, 已逐渐成为一个新的研究热点. Zhang 等 [6] 通过亲电取代将不同的官能团引入到自由基加成苯环 的碳纳米管表面, 共价功能化后的碳纳米管可以作为基 体, 进行进一步的修饰, 包覆聚合物或是负载贵金属粒 子等, 表明功能化后的碳纳米管作为功能材料具有非常 广阔的应用空间. Li 等 [7] 通过重氮化反应将对氨基苯硫 酚修饰到碳纳米管上, 然后再负载 Pd 粒子, 功能化的碳 纳米管不仅增加了对贵金属粒子的锚定位, 而且巯基与 贵金属粒子的强结合力可以有效地阻止贵金属粒子的 脱落.…”
Section: 引言unclassified